Zirconium dioxide: synthesis alternatives and biomedical applications - Andrade-Guel, Marlene Larisa (Universidad Autónoma de Tamaulipas, 2019)
Among the different ceramic materials, zirconium dioxide (ZrO2) stands out, due to its applications in the medical, chemical and pharmaceutical areas. This is possible, since it is an amphoteric material with three crystalline phases: monoclinic, tetragonal and cubic, which have different properties. The objective of this work was to analyze the fundamentals of the different methods used for the synthesis of ZrO2, and its main biomedical applications. The main methodologies used include the hydrothermal, precipitation, solvothermal and sol-gel processes. The use of ultrasound energy and microwave radiation allows the reduction in reaction times, and provides greater energy efficiency to the process and a lower environmental impact. The synthesis method modifies the properties of ZrO2, which is used to develop different applications, including bone replacements, dental prostheses and drug release.